Tuning Molecular Solar Thermal Properties by Modification of a Promising Norbornadiene Photoswitch. Issue 13 (21st March 2019) - Jevric, Martyn; Wang, Zhihang; Petersen, Anne U.; Mansø, Mads; Sumby, Christopher J.; Nielsen, Mogens Brøndsted; Moth‐Poulsen, Kasper
Abstract : Carefully targeted modifications to the norbornadiene‐quadricyclane couple should give molecules with great potential for solar energy storage. Here we report the synthesis of derivatives of a well‐studied compound, 2‐cyano‐3‐anisyl norbornadiene (NBD5 ). The conjugation was extended by conversion of the nitrile into acrylonitrile and acrylate derivatives over two steps. Despite red‐shifting the absorbance properties, the metastable quadricyclanes exhibited extremely short lifetimes. Meanwhile, treatment of NBD5 with acetyl halides in the presence of aluminum trihalides led to the formation of 7‐acetyl norbornenes through a Wagner–Meerwein rearrangement. Subsequent transformations made it possible to synthesise norbornadienes with varying degrees of steric bulk at the 7‐position of the molecular scaffold. It was found that the bulkier this group was, the more stable the quadricyclane form. This reaction sequence allows for the synthesis of norbornadiene derivatives which are more suited to molecular solar thermal applications in domestic heating despite providing a slightly lower energy density. Abstract : Substitution at C7 of a norbornadiene through a Wagner–Meerwein rearrangement allowed for formation of derivatives with longer life times for the corresponding quadricyclane metastables. This stability corresponded to the steric bulk of the substituent. Meanwhile, extension of the conjugation at C2 by modification to the nitrile group gave products with much shorter quadricyclane lifetimes.